2021
DOI: 10.3390/molecules26154687
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metal Nanoparticles Stabilized by Hyper-Cross-Linked Polystyrene as Effective Catalysts in Hydrogenation of Arenes

Abstract: This work is addressing the arenes’ hydrogenation—the processes of high importance for petrochemical, chemical and pharmaceutical industries. Noble metal (Pd, Pt, Ru) nanoparticles (NPs) stabilized in hyper-cross-linked polystyrene (HPS) were shown to be active and selective catalysts in hydrogenation of a wide range of arenes (monocyclic, condensed, substituted, etc.) in a batch mode. HPS effectively stabilized metal NPs during hydrogenation in different medium (water, organic solvents) and allowed multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The solubility of naphthalene in the nonpolar solvents was better than that in the polar solvents. As a nonpolar solvent, n -hexane was more conducive to naphthalene hydrogenation . In addition, n- alkanes performed better than cycloalkanes for the hydrogenation of naphthalene because of their molecular structure.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The solubility of naphthalene in the nonpolar solvents was better than that in the polar solvents. As a nonpolar solvent, n -hexane was more conducive to naphthalene hydrogenation . In addition, n- alkanes performed better than cycloalkanes for the hydrogenation of naphthalene because of their molecular structure.…”
Section: Resultsmentioning
confidence: 98%
“…As a nonpolar solvent, n-hexane was more conducive to naphthalene hydrogenation. 55 In addition, n-alkanes performed better than cycloalkanes for the hydrogenation of naphthalene because of their molecular structure. Compared with n-hexane, the conversion of naphthalene was very low in the solvent of ntridecane and n-hexadecane due to their high boiling points.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It was found that NA-based HAPs can serve as a support for Pd NPs. In our previous work [ 21 , 39 ], we showed that small Pd NPs at 2–4 nm in diameter can be formed after reduction in a hydrogen flow at 300 °C of Pd-precursor on commercial hyper-crosslinked polystyrene. In this study, to demonstrate the effect of functional groups of the synthesized novel NA-based polymers on the formation of the metal NPs, we chose liquid-phase reduction under mild conditions (0–5 °C, NaBH 4 ) to protect polymers’ functionalities (-OH, -SO 3 R, or -NO 2 groups) from destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial HAPs with various functional groups and high mechanical, thermal, and chemical stability are available [ 17 ]. Such amorphous polymers were successfully used as catalytic supports for both Pd complexes and grown Pd 0 NPs due to their high specific surface area (SSA), developed porosity, and double (hydrophilic-hydrophobic) surface character [ 18 , 19 , 20 , 21 ]. The presence of functional groups on the HAPs surface was found to enhance the metal dispersion, while the developed porous structure provided quick diffusion of reagents into the pores and facilitated interaction with active centers.…”
Section: Introductionmentioning
confidence: 99%